Toxic pesticide in cigarettes - Abd Razak, Dzulkifli (1997)
THE RECENT ADMISSION BY LIGGET Group Inc. in the United States confirmed the longheld suspicion that cigarettes contain a potpourri of hazardous substances. In an unprecedented maove, Ligget reached a pact with more than 20 states in the United States which are currently suing the tobacco industry to recoup medical funds spent in treating smokingrelated illnesses (such expenditure could amount to an estimated US$600 million a year). This was a landmark event, because for the first time, the true anatomy of the tobacco industry was exposed to the public. Ligget broke ranks with the rest of the tobacco industry by making available "a treasuretrove of potentially incriminating documents that the state and local governments will rely on in the city and county lawsuits" against other tobacco companies.